Paint and surface coatings : theory and practice. - Lambourne, R. (Ronald), 1929-; Strivens, T. A. (Woodhead Pub., 1999)
An updated version of a respected and established text. This edition contains two completely new chapters dealing with the use of computers in the paint industry and with the increasingly important subject of health and safety. The chapter on pigments has also been re-written.